Association of environmental markers with childhood type 1 diabetes mellitus revealed by a long questionnaire on early life exposures and lifestyle in a case–control study. (December 2016) - Balazard, F.; Le Fur, S.; Valtat, S.; Valleron, A.; Bougnères, P.; Thevenieau, Dominique; Chatel, Corinne; Desailloud, Rachel; Bony-Trifunovic, Hélène; Ducluzeau, Pierre-Henri; Coutant, Régis; Caudrelier, Sophie; et al.
Abstract Background The incidence of childhood type 1 diabetes (T1D) incidence is rising in many countries, supposedly because of changing environmental factors, which are yet largely unknown. The purpose of the study was to unravel environmental markers associated with T1D. Methods Cases were children with T1D from the French Isis-Diab cohort. Controls were schoolmates or friends of the patients. Parents were asked to fill a 845-item questionnaire investigating the child's environment before diagnosis. The analysis took into account the matching between cases and controls. A second analysis used propensity score methods. Results We found a negative association of several lifestyle variables, gastroenteritis episodes, dental hygiene, hazelnut cocoa spread consumption, wasp and bee stings with T1D, consumption of vegetables from a farm and death of a pet by old age. Conclusions The found statistical association of new environmental markers with T1D calls for replication in other cohorts and investigation of new environmental areas. Trial registration Clinical-Trial.govNCT02212522 . Registered August 6, 2014.